Karakteristik Papan Partikel Menggunakan Perekat Tanin Mahoni Dengan Ekstender Pati: Characteristics of Particle Board Using Mahogany Tannin Adhesive with Starch Extender - Lestari, Andi Sri Rahayu Diza; Monica, Alfitra Rosa; Manggasa, Andika; Tandi, Lisa (Forestry Faculty of Hasanuddin University, 2025)
This study aimed to determine the characteristics of particleboard bonded using mahogany tannin adhesive plus starch extender. The particles used came from mangium wood, which was then bonded using mahogany tannin adhesive (TRF) with the addition of 2 concentrations of starch extender, 10% and 20%. The size of the particleboard produced was 25 cm x 25 cm x 1 cm (each in the dimensions of length, width, and thickness). Physical and mechanical property testing was carried out based on SNI 03-2105-2006. The results showed that the higher the concentration of starch extender addition to the TRF adhesive, the higher the internal bond value, as well as the thickness expansion of the resulting particleboard.